THE USE OF GROUP INVESTIGATION METHOD TO IMPROVE STUDENTS’ SPEAKING ABILITY AT ENGLISH DEPARTMENT OF SORONG MUHAMMADIYAH UNIVERSITY - Riski Amaliyah; Muhaiminah Akib; Rezkiah Hartanti (Qalam : Jurnal Ilmu Kependidikan, 2017)
This research is aimed to conduct research about using Group Investigation Method to improve students’ speaking ability. Therefore, the researcher observed in English Department of Sorong Muhammadiyah University. The researcher uses quantitative method and the design of this research used pre-experimental method with one group pre-test and post-test design. The sample of this research was taken from third semester of class C in Teacher and Trainning Education Faculty in English Department of Sorong Muhammadiyah University. The sample was taken with randomized sampling and consisted of 30 students. Based on the result teaching reading used collaborative strategy reading at the second year students of SMP Negeri 1 sorong. The researcher found that the teaching reading using collaborative strategy reading did not give much influence to students reading ability. With the use of Collaborative Strategy Reading in teaching and learning made the students very happy and they think that the strategy of reading was interested in improving the foreign language of them. They gave good response and active in the class. Where the mean score of pre test was 31,67 and the mean score of post test was 46,67 and the t – test was 12.5 and t - table was 1.714. Based on the analysis of the research, Collaborative Strategy Reading,did not give much influence to student reading ability.This statement was proved because in control group students also could improve their reading skill well at the second year students of SMP Negeri 1 Sorong When the t- test was 12.5 more high than t- table was 1.714.